Perspectives of Educated and Less-Educated Parents on EFL Teaching for Potentially Dyslexic Second-Grade Elementary Students - Dewi, Komang Rista Liani; Artini, Luh Putu; Ana, I Ketut Trika Adi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates how parents with different educational backgrounds support second-grade elementary students who are potentially struggling with dyslexia in learning English as a Foreign Language (EFL). The research explores their awareness of dyslexia and the strategies they employ to assist their children's language learning. Employing a qualitative case study design, data were gathered through classroom observations and semi-structured interviews with four parents at a school in central Singaraja. The findings indicate that educated parents tend to demonstrate greater involvement, including the use of digital tools, the establishment of structured study routines, and consistent communication with teachers. In contrast, less-educated parents commonly depend on repetition-based methods and hold the belief that their children’s challenges will pass over time.These contrasts highlight the importance of parental education in shaping support strategies and the need for stronger school-parent partnerships. The study also advocates for accessible resources and training to equip parents better to support their children’s literacy development, especially in EFL contexts.